Don’t Walk So Close to Me: Physical Distancing and Adult Physical Activity in Canada - Di Sebastiano, Katie M.; Chulak-Bozzer, Tala; Vanderloo, Leigh M.; Faulkner, Guy (Frontiers in Psychology, 2020)
Background: In response to the COVID-19 pandemic, physical distancing measures have been implemented globally. Canadians have been instructed to stay at home which has likely resulted in significant changes in their physical activity. Using data from a national physical activity tracking app (PAC app), we aimed to determine device-measured physical activity levels immediately prior to and following the implementation of physical distancing measures in Canada to provide evidence for the development of physical activity recommendations for future pandemics or second-wave infections. Methods: Demographic and physical activity data were extracted from the PAC app, using a 10-week (10 February to 19 April 2020) quasi-experimental design to determine changes in physical activity 4 weeks pre- and 6 weeks post-pandemic declaration. Weekly physical activity levels were monitored through wearable fitness trackers and health apps linked to the PAC app, to record moderate-to-vigorous physical activity (MVPA), light physical activity (LPA), and steps. Repeated measure ANOVA were used to determine changes over time (mean  SE). Findings: A total of 2,338 Canadians who were mostly 35-44 years old (26.6%), and female (90.2%) were included in the analysis. MVPA, LPA, and steps significantly declined immediately following the declaration of the pandemic (MVPA: pre-pandemic: 194.25.2 min, post-pandemic: 176.75.0min, p<0.001; LPA: pre-pandemic: 1000.517.0min, post-pandemic: 874.115.6min, p<0.001; steps: pre-pandemic: 48,625745 steps, post-pandemic: 43395705 steps, p<0.001). However, 6 weeks following pandemic declaration, MVPA (week 6: 204.45.4 min, p=0.498) had returned to pre-pandemic levels. LPA (week 6: 732.014.3 min, p=<0.001) and steps (week 6: 41,946763, p<0.001) remained significantly lower than pre-pandemic levels at week 6. Interpretation: Although MVPA returned to pre-pandemic levels, significant and sustained declines in incidental LPA and steps were observed. Attenuating the loss of incidental physical activity should be a public health priority in response to future pandemics or a second wave of a COVID-19 infection, as it may have significant long-term implications for the physical and mental health of Canadians.